Pengaruh Dukungan Sosial Teman Sebaya terhadap Penyesuaian Diri Santri di Pondok Pesantren - Novi; Muhimmatul Hasanah; Indah Fajrotuz Zahro (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2021)
This researcher aims to examine the effect of peer support on the adjustment of students at the Al-Adawiyyah Islamic boarding school for the daughter of Sunan Drajat. The approach used in this research is a quantitative approach with a simple linear regression type of research. The research sample was 65 in the al-adawwiyyah dormitory of the Sunan Drajat Islamic boarding school. The instrument of this study used a peer social support scale and a self-adjustment scale. The data analysis technique used statistics and hypothesis testing using a simple linear regression test. It begins with the assumption test, the Kolmogrov-Smirnov normality test and the linearity test. Based on the table of the results of the regression coefficient test, it can be seen that the value of t = 0.163, in addition to the Sig column or the independent significance variables and constants, the significance level is below 0.05. It can be obtained from the results of the R Square value or the value of the coefficient of determination of 0.553 or 55.3%. This means that peer social support has a significant effect on self- adjustment. In knowing how much the variables of peer social support affect the adjustment variable in the al-adawiyyah boarding school students of the Sunan Drajat Islamic boarding school. The subject level is in the medium category, as many as 5 students with a percentage of 8%. Meanwhile, the subject in the high category was 60 students with a percentage of 92%. In the peer social support scale, none of them fall into the low category. Through this norm, it can be seen that the subjects in this study were students who had significantly high peer social support, but the subjects tended to have peer social support.